2018
DOI: 10.5603/gp.a2018.0057
|View full text |Cite
|
Sign up to set email alerts
|

How to identify pregnant women at risk of pre-eclampsia? — a review of the current literature

Abstract: Pre-eclampsia remains a major cause of poor perinatal outcome worldwide. As administering acetylsalicylic acid in a high risk population reduces the risk of PE, it is essential to identify women at risk of PE. Several algorithms for PE risk assessment have been developed. They include maternal factors combined with uterine artery pulsatility index, mean arterial pressure, serum pregnancy-associated plasma protein-A, placental growth factor, and serum soluble fms-like tyrosine kinase-1. Beside PE prophylaxis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Preeclampsia is a severe complication of pregnancy that is characterized by elevated blood pressure, proteinuria, seizures, failure of multiple organs, and even death [1][2][3][4][5][6][7]. An accurate and early diagnosis of this condition is an unmet clinical need [8,9]. In 2014, Buhimschi et al demonstrated that urine proteins in patients with preeclampsia exhibited properties similar to amyloid [10].…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia is a severe complication of pregnancy that is characterized by elevated blood pressure, proteinuria, seizures, failure of multiple organs, and even death [1][2][3][4][5][6][7]. An accurate and early diagnosis of this condition is an unmet clinical need [8,9]. In 2014, Buhimschi et al demonstrated that urine proteins in patients with preeclampsia exhibited properties similar to amyloid [10].…”
Section: Introductionmentioning
confidence: 99%